2019
DOI: 10.1007/s12094-019-02060-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis outcomes after cancer immunotherapy

Abstract: Introduction: Neurological immune-related adverse events are a rare but potentially deadly complication after immune checkpoint inhibitor (ICI) treatment. As multiple sclerosis (MS) is an immune mediated disease it is unknown how ICI treatment may affect outcomes. Methods: We analyzed the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database for pembrolizumab, atezolizumab, nivolumab, ipilimumab, avelumab, and durvalumab two years prior their FDA approval until Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 47 publications
2
84
1
Order By: Relevance
“…In most phase III studies investigating ICI based treatments patients with pre-existing autoimmune diseases have [12]. A recent meta-analysis found that flares of MS during ICI treatment are rare, but severe [13]. To date, in our case, neither pembrolizumab nor ipilimumb lead to RRMS flares, despite cessation of treatment with fingolimod, while effectively treating cancer.…”
Section: Discussionmentioning
confidence: 68%
“…In most phase III studies investigating ICI based treatments patients with pre-existing autoimmune diseases have [12]. A recent meta-analysis found that flares of MS during ICI treatment are rare, but severe [13]. To date, in our case, neither pembrolizumab nor ipilimumb lead to RRMS flares, despite cessation of treatment with fingolimod, while effectively treating cancer.…”
Section: Discussionmentioning
confidence: 68%
“…4,24 The most common irAEs of the CNS includes encephalitis, aseptic meningitis, and myelitis. Some irAEs of the CNS are extremely rare, such as multiple sclerosis (MS), 25 posterior reversible encephalopathy syndrome, 26 neurosarcoidosis, 27 cerebral vasculitis, 28 Tolosa-Hunt syndrome, 29 and Vogt-Koyanagi-Harada syndrome. 30 Given the high fatality rate of irAEs of the CNS (encephalitis, 6.3-12.8%; meningitis, 7.4-8.3% 19,20 ), patients should be recognized promptly and treated with immune-modulating agents without delay.…”
Section: Neurological Iraes Affecting the Cnsmentioning
confidence: 99%
“…Another case, described by Gettings et al, was of a 56-year-old male with MS with recurrent melanoma after multiple resections; he was treated with ipilimumab who developed two MS flare-ups, leaving him with disability from MS relapse but had remission of melanoma on PET scan 14 . Garcia et al conducted a retrospective analysis capturing 42,529 adverse events with the use of ICI with 13 cases identified with MS. Of the 13, eight had a previous diagnosis of MS. All the patients in their analysis experienced progression of their MS, and two patients died following their MS relapse 15 .…”
Section: Discussionmentioning
confidence: 99%